Factors Affecting Response Quantity, Quality and Speed in Questions Asked via Online Social Networks - Teevan, Jaime; Morris, Meredith Ringel; Panovich, Katrina (Proceedings of ICWSM 2011, 2011)
Social networking tools enable people to easily ask ques-tions of large groups of personal acquaintances, but the ef-fectiveness of doing so depends in part on how the question is phrased. In this paper we present a study in which 282 participants posted variants of the same question as their status message on Facebook. We analyze the quantity, quality, and speed of the responses each variant received. We find that by ending an information need with a question mark, explicitly scoping the audience, and being succinct, a person can increase the likelihood of quickly receiving many high-quality answers.